A Malaysian perspective on Qur'anic governance : family autonomy vs state intervention. - Kamaruddin, Zaleha (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2010)
Good governance' is considered a crucial element for peace and development of societies, because it implies good order and good policies. In the context of the family institution, this is a must in order to ensure that the basic unit of society is protected from destruction. In relationtothis, most scholars have acknowledged that allover the world, the family has undergone radical transformations in response to the changing socio-economic environment. However, the breadth and depth of this change in the realm of good govemance has often been neglected. This article begins by examining contemporary challenges confronting the family institution. justifications for state intervention through the existing family laws in Malaysia as one of the mechan.isms in protecting the family will also be analysed. To ensure that family stability can be maintained and developed,'qur'anic governance' is proposed as a mechanism for social transformation